Peran Fear of Missing Out (FoMO) Sebagai Moderator Antara Kesejahteraan Subjektif dengan Narsisme pada Dewasa Muda Pengguna Instagram - Zulfa, Daffa Aulia; Kartasasmita, Sandi (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Social media are a forum for people to search for and share information in the form of writing, videos and images. The presence of social media has given rise to a digital anxiety known as Fear of Missing Out (FoMO). One of the popular applications is Instagram. Considering the large number of users of the Instagram application, researchers are interested in conducting research on the role of Fear of Missing Out (FoMO) as a moderator between Subjective Well-Being and narcissism in young adult Instagram users. The research was conducted using a non-probability sampling method (purpose sampling) and respondents aged 20-30 years used the Google Form platform. Data processing uses SPSS with reliability test parameters. Based on the results of data analysis, there is a negative and significant relationship between Subjective Well-Being and Fear of Missing Out (FoMO) and there is a positive and significant relationship regarding the relationship between narcissism and FoMO among Instagram users among young adults aged 20- 30 years. The results of this research are that FoMO is not related to SWB, while Narcissism can be a moderator of the respondent's Fear of Missing Out (FoMO) trend.